Knowledge and practices of the use of honey for acute respiratory infections - Ouaamr, Ahmed; Mouna Mekkaoui; Hajar El Ouadni; Mohammed Hassar; Yahya Cherrah; Katim Alaoui (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Honey has been used for centuries as both a food and a traditional remedy. Known for its antimicrobial, anti-inflammatory, and antioxidant properties, honey is frequently used to treat various ailments, including respiratory infections. In Morocco, especially in regions like Guelmim, the use of honey is deeply rooted in cultural practices. Despite this, there remains limited scientific data on public knowledge and practices regarding honey as a treatment for acute respiratory infections (ARIs). Understanding these aspects can help bridge traditional medicine with evidence-based healthcare strategies. This study aimed to clearly assess the population’s level of knowledge and practices related to the use of honey as a treatment for ARIs in the Guelmim region of southern Morocco. METHODOLOGY: A cross-sectional survey was conducted from September 2022 to July 2024 among 834 participants from Guelmim. The questionnaire, available in French and Arabic, was administered online and in person. Data were analyzed using the chi-square test and logistic regression. RESULTS:The study found that 82% of respondents use honey for respiratory issues, with 46.2% consuming it occasionally. Preference for Saharan plant honey was noted in 38% of respondents. Honey was commonly used for sore throat (57.7%) and cough (32.7%). A significant association between honey use and knowledge level was found (β = 2.96; ORa = 37.28; p < 0.05), although only 34.2% had high knowledge of its benefits. CONCLUSION: Age, education, and chronic disease significantly influenced knowledge levels. Most respondents (67.3%) used honey as a complementary treatment for ARIs.